If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -5) = 3x + 13 Reorder the terms: 4(-5 + 2x) = 3x + 13 (-5 * 4 + 2x * 4) = 3x + 13 (-20 + 8x) = 3x + 13 Reorder the terms: -20 + 8x = 13 + 3x Solving -20 + 8x = 13 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -20 + 8x + -3x = 13 + 3x + -3x Combine like terms: 8x + -3x = 5x -20 + 5x = 13 + 3x + -3x Combine like terms: 3x + -3x = 0 -20 + 5x = 13 + 0 -20 + 5x = 13 Add '20' to each side of the equation. -20 + 20 + 5x = 13 + 20 Combine like terms: -20 + 20 = 0 0 + 5x = 13 + 20 5x = 13 + 20 Combine like terms: 13 + 20 = 33 5x = 33 Divide each side by '5'. x = 6.6 Simplifying x = 6.6
| 10P+8=5P-2 | | 13-22=-3x | | 16-3b=0 | | 5=7Y-5Y-3 | | y^2+13y+12= | | 16-36=0 | | 10B-11B=0 | | 2(-4+p)=-8.2+1.8p | | -4=-9+8-29 | | x^2+47x+56=0 | | H(x)=2x^3+5x^2-31x-15 | | -15n^2+13=-10n^2-6n | | 6x(3x-4)(2x+5)= | | x^6-243=0 | | -4=9+8-29 | | 3n^2=-8 | | 51a-56=44 | | 4=9+8-29 | | 10v^7+26v^6+12v^5= | | (m-5)x^2-(m+2)x+(m-1)=0 | | -3(3s-3)-9=-2(8s+2)-2 | | -x+5=29 | | 5x^3+3x^2-10x-6= | | -8x+12=-4x+32 | | 4n=17n+25 | | Y=24-3 | | 3r^2=-7 | | 3(2m-3)=4(7-m) | | 25-36w^2= | | 4(a+3)-y(a+3)= | | 5z+4z=8z-9 | | 19x=774-19x |